1988
DOI: 10.1210/jcem-67-2-395
|View full text |Cite
|
Sign up to set email alerts
|

Medical Management of Acromegaly Due to Ectopic Production of Growth Hormone-Releasing Hormone by a Carcinoid Tumor*

Abstract: A 59-yr-old woman with a disseminated carcinoid tumor was evaluated for acromegaly. She had previously undergone a hypophysectomy for acromegaly and an enlarged pituitary, with a reduction in her serum GH levels from 100 to 4 micrograms/L. Recurrence of acromegalic symptoms 2 yr later was accompanied by elevated serum GH (16 micrograms/L) and insulin-like growth factor I (IGF-I; 528 micrograms/L) and plasma GHRH levels (12 micrograms/L; normal, less than 30 ng/L). Computed tomographic scan did not reveal pitui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
27
0
1

Year Published

1989
1989
2010
2010

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(32 citation statements)
references
References 20 publications
4
27
0
1
Order By: Relevance
“…Although our initial study (1) was performed using synthetic GRH(1-44)-NH2, recent characterization of plasma from a patient with ectopic GRH secretion associated with a carcinoid tumor revealed that the majority of GRH immunoreactivity was in the form of GRH(3-40)-OH (3). In the present report we also provide evidence for similar metabolism in another model of GRH hypersecretion, the transgenic hGRH pig.…”
Section: Introductionsupporting
confidence: 63%
See 1 more Smart Citation
“…Although our initial study (1) was performed using synthetic GRH(1-44)-NH2, recent characterization of plasma from a patient with ectopic GRH secretion associated with a carcinoid tumor revealed that the majority of GRH immunoreactivity was in the form of GRH(3-40)-OH (3). In the present report we also provide evidence for similar metabolism in another model of GRH hypersecretion, the transgenic hGRH pig.…”
Section: Introductionsupporting
confidence: 63%
“…The action of these enzymes, however, emphasizes the importance of the development of resistant analogues for potential therapeutic and animal science use. Indeed, we have recently characterized the plasma GRH immunoreactivity in a patient with acromegaly due to an ectopic GRH-producing tumor (3). Plasma IR-GRH levels before treatment were nearly 10 ng/ml, but after HPLC separation, intact, native GRH forms were shown to make up only 5-10% of the total circulating GRH immunoreactivity.…”
Section: Resultsmentioning
confidence: 99%
“…Octreotride therapy was usually given to patients with disseminated GHRH-secreting tumours that could not be removed completely by surgery. Normalization of GH and IGF-I levels was achieved in most of the treated patients (Ch'ng et al, 1985;von Werder et al, 1986von Werder et al, , 1987Barkan et al, 1988;Melmed et al, 1988;Bertherat et al, 1994;Lefebvre et al, 1995), whereas slight (Moller et al, 1989; or no improvement (Southgate et al, 1988;Ezzat et al, 1994) was reported in the others. An undetectable plasma GHRH level was never achieved in any patient, although significant decreases in the circulating peptide were reported (Fig.…”
Section: Therapymentioning
confidence: 94%
“…In fact, therapy aimed only at controlling GH hypersecretion is invariably unsuccessful. Pituitary surgery, usually performed because of misdiagnosis, was reported in eight patients (uz Zafar et al, 1979;Thorner et al, 1982;von Werder et al, 1984;Schulte et al, 1985;Barkan et al, 1986;Melmed et al, 1988;Ezzat et al, 1994Genka et al, 1995 and in all cases residual GH hypersecretion persisted after surgery. Dopaminergic drugs, which are completely ineffective on the underlying neoplasm, have been used in eight patients (Losa et al, 1993): only two showed some clinical and biochemical amelioration of acromegaly.…”
Section: Therapymentioning
confidence: 99%
See 1 more Smart Citation